The effect of inspiratory muscle training at high altitude on arterial oxygen saturation and performance of endurance runners - Mohammadi Rezaei, R.; Mirdar, S. (Medicina dello Sport, 2016)
BACKGROUND: The aim of this study was to investigate the effect of inspiratory muscle training at high altitude on peripheral capillary oxygen saturation and performance among endurance runners. METHODS: The study was carried on a group of 12 endurance male runners (age 24.4±3.1 years, height 180.5±4.23 cm, weight 66.75±3.46 kg, Body Mass Index 20.53±1.07 kg/m2) from the Iranian national team were randomly divided into case and control group in hypoxic condition. Exhausting 1500-m running tests, Strength Index and arterial oxygen saturation tests were taken before and 24 hour after training period. The training program includes the same continuous, interval, aerobic and resistance training exercises for the two groups. Runners performed 16 training session per week in high altitude within four weeks. RESULTS: Data were analyzed by analysis of variance (P=0.05). Inspiratory muscle training at hypoxia due to significant decrease in 1500-m running performance, inspiratory muscle strength and peak inspiratory flow in both group, but the differences in volume and peripheral capillary oxygen saturation were not significant (P=0.05). CONCLUSIONS: This study suggests that using inspiratory muscle training along with specified training in hypoxia increases inspiratory muscle strength and peak inspiratory flow pressure meanwhile it decreases ventilation and 1500-m running time at lower altitude.